(untitled) (The University of Nairobi Journal of Language and Linguistics, 2025)
This paper discusses the major themes and implied meanings behind the names given to children in the culture of the Mafa, a community that lives in the Far-North Region of Cameroon. While naming their children, the Mafa people create a way to speak to the world. Naming is not a haphazard process, nor is it done for the pleasure of having this or that name. Giving a name to a child is a fervent commitment to bringing about a certain change in the way the world is. The present study aims to show that naming or bearing a name in the Mafa culture is performing an act. It is a form of oral literature revolving around themes such as death, suffering or illness, jealousy, joy, consolation, pride, and prayers addressed to God on specific issues. The data for the present study were collected through document analysis (exploitation of an existing checklist of names), observations, and interviews.